Single High Intensity Focused Ultrasound Session as a Whole Gland Primary Treatment for Clinically Localized Prostate Cancer: 10-Year Outcomes - Ksenija Limani; Fouad Aoun; Serge Holz; Marianne Paesmans; Alexandre Peltier; Roland van Velthoven (Prostate Cancer)
Objectives. To assess the treatment outcomes of a single session of whole gland high intensity focused ultrasound (HIFU) for patients with localized prostate cancer (PCa). Methods. Response rates were defined using the Stuttgart and Phoenix criteria. Complications were graded according to the Clavien score. Results. At a median follow-up of 94months, 48 (44.4%) and 50 (46.3%) patients experienced biochemical recurrence for Phoenix and Stuttgart definition, respectively. The 5- and 10-year actuarial biochemical recurrence free survival rates were 57% and 40%, respectively. The 10-year overall survival rate, cancer specific survival rate, and metastasis free survival rate were 72%, 90%, and 70%, respectively. Preoperative high risk category, Gleason score, preoperative PSA, and postoperative nadir PSA were independent predictors of oncological failure. 24.5% of patients had self-resolving LUTS, 18.2% had urinary tract infection, and 18.2% had acute urinary retention. A grade 3b complication occurred in 27 patients. Pad-free continence rate was 87.9% and the erectile dysfunction rate was 30.8%. Conclusion. Single session HIFU can be alternative therapy for patients with low risk PCa. Patients with intermediate risk should be informed about the need of multiple sessions of HIFU and/or adjuvant treatments and HIFU performed very poorly in high risk patients.